Projected cancer risks potentially related to past, current, and future practices in paediatric CT in the United Kingdom, 1990–2020 - Journy, Neige M Y (Br J Cancer, 2017)
BACKGROUND: To project risks of developing cancer and the number of cases potentially induced by past, current, and future computed tomography (CT) scans performed in the United Kingdom in individuals aged <20 years. METHODS: Organ doses were estimated from surveys of individual scan parameters and CT protocols used in the United Kingdom. Frequencies of scans were estimated from the NHS Diagnostic Imaging Dataset. Excess lifetime risks (ELRs) of radiation-related cancer were calculated as cumulative lifetime risks, accounting for survival probabilities, using the RadRAT risk assessment tool. RESULTS: In 2000–2008, ELRs ranged from 0.3 to 1 per 1000 head scans and 1 to 5 per 1000 non-head scans. ELRs per scan were reduced by 50–70% in 2000–2008 compared with 1990–1995, subsequent to dose reduction over time. The 130 750 scans performed in 2015 in the United Kingdom were projected to induce 64 (90% uncertainty interval (UI): 38–113) future cancers. Current practices would lead to about 300 (90% UI: 230–680) future cancers induced by scans performed in 2016–2020. CONCLUSIONS: Absolute excess risks from single exposures would be low compared with background risks, but even small increases in annual CT rates over the next years would substantially increase the number of potential subsequent cancers.